Role of matrix metalloproteinases in dental caries, pulp and periapical inflammation: An overview - Atul Jain; Rachana Bahuguna (Elsevier, 2015)
Matrix metalloproteinases (MMPs) are a group of more than 25 secreted and membrane bound enzymes that represent class of enzymes responsible for degradation of pericellular substrates. They have been isolated from dentine, odontoblasts, pulp and periapical tissue. They play an important role in dentine matrix formation, modulating caries progression and secondary dentine formation. Earlier microbial proteolytic enzymes were believed to be responsible for degradation of dentine organic matrix, but lately the accumulated body of evidence suggests that MMPs have an important role in the process. During normal tissue modelling, differentiation during development, in modulating the cell behaviour, maintaining homeostasis and in numerous extracellular pathologic conditions, MMPs tends to be an equally important participant. Odontoblasts secrete some of the essential MMPs for both physiologic and pathologic conditions. MMPs also appear to be a participant in the process of reversible and irreversible pulpitis. Although they tend to have low expression and activity in adult tissues but at the onset of any destructive pathologic process, their production shoots up. They appear to have a significant presence during times of inflammation in the periapical region as well. We take a look at the various factors and evidence pointing towards the role of MMPs in the progression of caries, pulpal and periapical inflammation.